Interpreting Revelation and other apocalyptic literature: an exegetical handbook - Pate, C. Marvin (Handbooks for New Testament exegesis, 2016)
The genre and figures of speech of apocalyptic literature -- The historical background of prophetic-apocalyptic books -- The function of apocalypticism and the theme of Israel's story -- Preparing to interpret the text -- Interpreting biblical apocalyptic literature -- Communicating a passage in Revelation -- From text to sermon : two examples -- Selected sources.